PENGARUH TIPE NUMBER HEAD TOGETHER TERHADAP HASIL BELAJAR PESERTA DIDIK DALAM PKn KELAS V SD - Anwar J, Matla’ul; Utami, Sri; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The problem in this research is "What is the Influence of application of type numbered head together to result of learning pkn student of class V Alementary School 01 river raya?". This research uses experimental method of quasi-experimental type with experimental design of Non-Equivalent Control Group Design. The population of all students in grade V of River Raya. Sampling is non probability sampling type purposive sampling is student in class V State Elementary School 01 River Raya. Technique of data collection using measurement technique form using objektive test. The result of data processing is obtained by mean of pre-test of control class 58,42 and mean experiment class pre-test 71,2. hypothesis test results using t-test (pollend variance) t arithmetic t-count= 5,5324 for α=5% obtained t table amounted to 1.6736, which means t count> t table (5,5324> 1.6736), then Ha accepted. So, it can be concluded Means there is influence Numbered Head Together on student learning outcomes on learning Citizenship Education in class V Alementary School 01 Sungai Raya. From the calculation of effect size (ES), obtained ES of 1, 04 (one point zero four) with high criteria. This means that learning by applying the Numbered Head Together type has a high effect on students' learning outcomes. Keyword : Influence, Numbered Head Together, Learning outcomes